Household Waste Management among Riverside Communities and other Determinants - Aprizal Satria Hanafi; Qomariyatus Sholihah; Martina Martina; Ema Novita Deniati (Media Kesehatan Masyarakat Indonesia, 2018)
Littering was recognized as an important cause of environmental pollution and was related to health problems. Banjarmasin city has been achieved the predicate of Adipura in 2015, but in reality there were still many drainage that clogged because of the pile of garbage, especially in the river. Management and disposal of household waste was an important issue in the city of Banjarmasin. The purpose of this study was to identify socioeconomic and demographic factors related to family members’ knowledge, practice, and behavior related to household waste management and produce corrective action plans. This study uses cross-sectional design. The study population is eople in the city of Banjarmasin who live on the edge of the river and meet the sample inclusion and exclusion criteria. Sampling was done using multistage random sampling method. Binary logistic regression was used for data analysis. We found that education level, household income, and sex were independently linked to littering. We also found that communities have unsafe knowledge, practices, and behaviors in relation to waste management. This study concludes that promotion of environmental information and public education on proper waste disposal needs to be done to improve the health and safety of the community environment